The role of roxithromycin in the treatment of respiratory tract infections: a comprehensive overview - Bhatti, Sumit; Ramkumar, Thalapathy; Khan, Seemab; Patil, Nikita (International Journal of Research in Medical Sciences, 2024)
Respiratory tract infections (RTIs) represent a substantial global health burden. Antibiotics, including macrolides like roxithromycin, are frequently prescribed to treat these infections. Roxithromycin exhibits bacteriostatic and bactericidal properties by disrupting bacterial protein synthesis. It has a better pharmacokinetic profile than erythromycin and demonstrates satisfactory tissue penetration and distribution. In addition to its antimicrobial action, roxithromycin displays anti-inflammatory properties, modulates neutrophilic actions, reduces pro-inflammatory cytokines, and inhibits mucus secretion and synthesis. These mechanisms contribute to its efficacy in treating a spectrum of RTIs, including sinusitis, pharyngotonsillitis, chronic rhinosinusitis, pneumonia, and bronchiectasis. Clinical studies have consistently demonstrated the effectiveness and tolerability of roxithromycin. Overall, roxithromycin offers a multifaceted approach to target both the microbial and inflammatory components of RTIs. Hence, this review aims to provide an overview of the pharmacokinetics and pharmacodynamics, as well as the efficacy and tolerability of roxithromycin in treating RTIs.